A Longitudinal Twin and Sibling Study of Associations between Insomnia and Depression Symptoms in Young Adults - Gregory, Alice M. (Sleep, 2016)
STUDY OBJECTIVES: To estimate genetic and environmental influences on the associations between insomnia and depression symptoms concurrently and longitudinally. METHODS: Behavioral genetic analyses were conducted on data from the British longitudinal G1219 twin/sibling study. One thousand five hundred fiftysix twins and siblings participated at Time 1 (mean age = 20.3 years, SD = 1.76). Eight hundred sixty-two participated at Time 2 (mean age = 25.2 years, SD = 1.73 years). Participants completed the Insomnia Symptoms Questionnaire and the Short Mood and Feelings Questionnaire to assess symptoms of insomnia and depression respectively. RESULTS: Genetic effects accounted for 33% to 41% of the variance of the phenotypes. The phenotypic correlations were moderate (r = 0.34 to r = 0.52). The genetic correlations between the variables were high (0.73–1.00). Genetic effects accounted for a substantial proportion of the associations between variables (50% to 90%). Non-shared environmental effects explained the rest of the variance and covariance of the traits. CONCLUSIONS: While genetic effects play a modest role in insomnia and depression symptoms separately, they appear to play a more central role in concurrent and longitudinal associations between these phenotypes. This should be acknowledged in theories explaining these common associations. CITATION: Gregory AM, Rijsdijk FV, Eley TC, Buysse DJ, Schneider MN, Parsons M, Barclay NL. A longitudinal twin and sibling study of associations between insomnia and depression symptoms in young adults. SLEEP 2016;39(11):1985–1992.